Florida Solid and Hazardous Waste Regulation Handbook: State Agencies - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
Four state agencies are primarily involved in solid and hazardous waste management and pollution control: Department of Environmental Protection (DEP), Department of Agriculture and Consumer Services (DACS), Department of Health (DOH), and Department of Community Affairs (DCA). This is EDIS document FE464, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.